Optimization of Diagnosing Gastroesophageal Reflux Disease in Adolescents Using GerdQ Questionnaire - T.A. Kriuchko; I.M. Nesinа (Zaslavsky O.Yu., 2015)
Objective: to study the sensitivity and specificity of GerdQ questionnaire for the diagnosing gastroesophageal reflux disease in adolescents in the outpatient. Materials and methods. A survey of 95 adolescents with complaints from the upper gastrointestinal tract was performed. After filling out the questionnaire, all children were examined by a pediatric gastroenterologist with the establishment of the preliminary diagnosis of gastroesophageal reflux disease. To confirm the diagnosis the patients were undergone instrumental tests (esophagogastroduodenoscopy, pH-meter). These results of objective specialist's examination and additional research were compared with the results of GerdQ questionnaire. Results. The sensitivity of GerdQ questionnaire was 68.7 %, specificity was 92.3 %